IT Productivity Paradox pada Perguruan Tinggi Swasta (Jurnal Ilmiah Teknologi Informasi Asia, 2018)
Policy for Information Technology (IT) implementation on Higher Ed. Institution should be supported by an analysis about the impact of IT Implementation on Higher Ed. Institution Productivity. IT Implementation tends to be a trend for nowadays Institution, where almost all of them are doing IT Implementation without cares for the high cost and resources spent on it. Which result will be a failure in IT investment because of a rash policy and decision for IT Implementation made by institution board director.IT Productivity Paradox is a relatively new perspective in IT Governance which purpose is to identify the contribution of IT to productivity. The natures of IT Implementation are high cost and plenty of people involved in it, which raise a question for policymaker whether cost and resource allocated for IT Implementation, is a success or a failure investment. The purpose of this research is to develop a conceptual model that explain all variable which impacted IT Implementation on increasing Productivity of Higher Ed. Institution by using direct and indirect approaches. We hope by using this model, Institution board director will be able to avoid and minimized the failure of IT Implementation investment or prevent the happenings of IT Productivity Paradox.